Zigbee network parameters effectness on control system behavior Assistant Professor Eng. Saad - et. al., Abdalratha Makki , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we perform extensive network evaluation by creating different scenarios (using different topologies), to observe the effect of some parameter at MAC and application layers such as rate of data transmit, delay, throughput and end to end delay with three promising topologies in ZigBee (sensor/actuator) network. This paper aims to leverage wireless devices for NCSs in industrial applications. To achieve this, industrial area was chosen (Path along the bank of the Medical City at Tigris river) to implement and simulate the proposed network and demonstrate the impact of these parameters by (Using OPNET IT Guru Academic Edition) network simulation tool.The goal is to highlight the effect of Zigbee network parameters in the two layers (Mac and PHY) on the (sensor gather data) to the control center and return a control signal to a controller device(actuator) set to perform a specific function in an attempt to reach the highest performance in industrial system have been chosen and achieve the stability state of this industrial systems.Results of three ZigBee topologies (star, mesh & mesh1 and tree) showed that star topology is more efficient and best suited compared with mesh and star topologies for IEEE 802.15.4/ ZigBee standard due to measured parameters (Average end to end delay (second), Average Data dropped rate (bits/second)) that showed highest results for star topology as well (see Comparative performance table).